Crucial factors affecting reproduction and culture of Hippocampus barbouri (Jordan and Richardson 1908) - Abd Halid, Nur Fatihah (2018)
Hippocampus barbouri is one of the ten seahorses species found in Malaysia and listed in Appendix II of the Convention on the International Trade of Endangered Species of Wild Fauna and Flora (CITES). Its mere existence is threatened by human, being exploited to fulfil demands from traditional Chinese medicine (TCM) and ornamental trades. It is on demands regardless whether it comes from the wild or cultured. Thus, the establishment of seahorse aquaculture is imminent. Since, there is no documented report on seahorse aquaculture in Malaysia, this study focused on several most important aspects in order to develop suitable technique for the reproduction and culture of H. barbouri. During the acclimatization of wild H. barbouri, two common causal factors for mortality were gas bubble disease (GBD) and annelid infestation. Therefore, it was a necessity to overcome this problem to proceed with this study. GBD was taken care by manual removal of gas from the male brood pouch, while annelid infestation was treated with formalin. Subsequent experiment was conducted using different culture systems to determine the most suitable system for the maintenance and breeding of this seahorse. Findings shows that minimum water depth required for the successful spawning of H. barbouri is 0.38 m, while the most suitable diet for seahorse broodstock is shrimp post-larvae. The second objective of the study was to observe and describe the morphological development of H. barbouri from juvenile until maturity. Isometric growth pattern was observed during the early developmental stage until it reaches 141 day after birth (DAB), showing the first sign of sex differentiation. Then, from 141 until 168 DAB, male and female H. barbouri recorded different growth pattern. The onset of maturity was observed at 164 DAB with the presence of fully developed brood pouch in male, with standard length and wet weight of 7.16 cm and 1.47 g, respectively. In the next objective, the effects of physical factor such as culture system, stocking density and salinity on the growth and survival of H. barbouri during critical stage (1 to 56 DAB) were investigated. Newborn H. barbouri cultured in system with combination of hang-on and under-gravel filter showed the best growth with standard length of 3.74 cm and survival of 75%. Using this culture system, different seahorse stocking densities and water salinities were tested. Results shows that at stocking density of 0.5 seahorse L-1 (1 seahorse per 2 L) and salinity of 24 ppt produced the best growth and survival of H. barbouri. Scarcity of natural seawater supply has prompted the study on the potential of using artificial sea-salt for the culture of H. barbouri. Newborn H. barbouri cultured in seawater made from commercial artificial sea-salt known as Red Sea Coral Pro Salt (RSCPS) showed the best growth with standard length increment of 3.13 cm. Element analysis showed that this commercial sea-salt contained similar elements to that of natural seawater. Feeding experiment was conducted to determine the effect of different Artemia enrichment on the growth and survival of newborn H. barbouri. Newborn fed with Artemia nauplii enriched either using cod liver oil in combination with thyroxine or potassium iodide produced the best growth and survival. A subsequent experiment was carried out to determine the effectiveness of feeding this enriched Artemia at different frequencies. Economically, enrichment of Artemia using cod liver oil in combination with thyroxine fed twice a week is highly recommended. This study also determine the potential of other feed item such cladoceran Daphnia for juvenile H. barbouri at the age of two month-old. In conclusion, seahorse H. barbouri can successfully breed in tank system with hang-on filtration unit, at a minimum water depth of 0.38 m. Broodstock of H. barbouri can be fed with either post-larvae shrimp or frozen Mysis for better reproductive performance. During the development of H. barbouri in captivity, critical period with high mortality was observed at 7-11 DAB, with prominent slow growth during the first two months. Hippocampus barbouri reared in control condition can reproduce at the age of 168-175 DAB. Tank with hang-on combined with under-gravel filter was the most effective tank system for the culture of H. barbouri during early stage at stocking density of 1 seahorse in 2 to 3 L volume. Salinity of 24 ppt was the most suitable salinity for the culture of H. barbouri. Red Sea Coral Pro Salt (RSCPS) and Red Sea Salt (RSS) can be used for the preparation of seawater for the culture of H. barbouri. At early stage, H. barbouri can be fed with Artemia nauplii enriched with cod liver oil and thyroxine at frequency of twice weekly. Frozen wild zooplankton or sub-adult Artemia were suitable live food for juvenile H. barbouri at the advance stage.